Halo-Independent Comparison of Direct Dark Matter Detection Data - Eugenio Del Nobile (Advances in High Energy Physics)
We review the halo-independent formalism that allows comparing data from different direct dark matter detection experiments without making assumptions on the properties of the dark matter halo. We apply this method to spin-independent WIMP-nuclei interactions, for both isospin-conserving and isospin-violating couplings, and to WIMPs interacting through an anomalous magnetic moment.